SECULARISM IN PAMUK’S SNOW; A POSTCOLONIALISM STUDY - Muh. Fajar (OKARA: Jurnal Bahasa dan Sastra, 2013)
Postcolonial criticism has always analyzed colonial power through the multifarious signs, metaphors and narratives of both the dominating and indigenous cultures, in other words, the cultural formations and representational practices can be understood as colonial discourses. Initially these discourses were examined primarily in terms of binary oppositions, as exemplified in Edward Said’s notion of Orientalism. This paper explores secularism as one part of binary oppositions opposed to religion in Pamuk’s Snow. Before the writer analyses secularism in this novel, thus he would like to discuss the concept of postcolonial theory, mimicry and hybridity, binary oppositions, then he focuses to discuss secularism as one part of binary opposition as opposed to religion in Pamuk’s Snow.